2014
DOI: 10.1161/circheartfailure.113.001041
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness, Central Pressures, and Incident Hospitalized Heart Failure in the Chronic Renal Insufficiency Cohort Study

Abstract: Background Chronic kidney disease (CKD) is associated with an increased risk of heart failure (HF). We aimed to evaluate the role of large artery stiffness, brachial and central blood pressure as predictors of incident hospitalized HF in the Chronic Renal Insufficiency Cohort (CRIC), a multi-ethnic multi-center prospective observational study of patients with CKD. Methods and Results We studied 2602 participants who were free of HF at baseline. Carotid-femoral pulse wave velocity (CF-PWV, the gold-standard i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 48 publications
2
65
0
2
Order By: Relevance
“…30 Among CRIC Study participants, elevated pulse wave velocity, also a measure of large artery stiffening similar to PP, was strongly associated with incident HF. 35 …”
Section: Discussionmentioning
confidence: 99%
“…30 Among CRIC Study participants, elevated pulse wave velocity, also a measure of large artery stiffening similar to PP, was strongly associated with incident HF. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Among CRIC participants, eGFR was inversely associated with PWV (29). Further, increased PWV was independently associated with a greater risk of hospitalization for incident HF (30).…”
Section: Aortic Stiffnessmentioning
confidence: 92%
“…Interestingly, the net reclassification improvement index was significant, meaning that measuring carotid-femoral PWV in CKD patients improves the prediction of risk beyond classical CV risk factors [17]. An association between aortic stiffness and CV events was also seen in the CRIC study [18]. …”
Section: Impact Of Aortic Stiffness On CV and General Prognosismentioning
confidence: 99%
“…If the majority of the clinical studies are consistent with the observation that large artery damage may contribute to the high incidence of CV diseases [15,16,17,18], the impact of large artery remodeling on CKD progression is still a matter of debate. In the present review, we will describe the large artery remodeling observed in CKD and its impact on renal, CV and general prognosis (table 2).…”
Section: Introductionmentioning
confidence: 99%